Cryoablation method for pulmonary artery sympathetic denervation in patients with pulmonary hypertension secondary to left sided heart disease: interventional technique, safety and results of the hospital phase - D. A. Feshchenko; B. A. Rudenko; A. S. Shanoyan; O. M. Drapkina; A. V. Kontsevaya; N. E. Gavrilova; F. B. Shukurov; V. V. Vlasov; D. S. Chigidinova; D. K. Vasiliev (Российский кардиологический журнал, 2019)
pulmonary artery pressure in Patients with Pulmonary Hypertension and Chronic Heart Failure.Materials and methods. Inclusion in the study (n=20) was based on the results of an echocardiographic study (systolic pressure in the pulmonary artery ≥35 mm Hg) and clinical assessment (NYHA ≥II FC heart failure). The procedure of pulmonary artery cryodenervation was performed at the bifurcation level of the main pulmonary trunk using single-point cryoablation catheter. The cryoablation was applied in a circular way around the pulmonary trunk at the bifurcation level, rotating the catheter tip with the pace of2 mm with temperature minus 75-80o C and time 120 s at each spot. The study endpoints were the changes in systolic pulmonary artery pressure, mean pulmonary artery pressure, pulmonary vessel resistance and 6 min walking test before and immediately after procedure.Results. We analyzed intermediate results of sympathetic fibers cryodestruction, located in the bifurcation of main pulmonary trunk. The mean systolic pulmonary artery pressure decreased from 40 [37; 44] tо 31 [28; 35] mm Hg (p<0,05), pulmonary vessel resistance decreased from 5,6 [4,9; 6,1] tо 3,9 [3,5; 4,5] WU (p<0,05) and improvement of 6 min walking test from 287 [233; 332] to 320 [276; 348] m (p<0,05) was observed. There were no cases of early deaths and specific complications.Conclusion. The cryoablation pulmonary denervation is a new promising treatment in patients with pulmonary hypertension. First clinical results demonstrate the safety of this procedure. Further randomized studies are required to confirm the efficacy of PDCM. However, today we can see decrease of hemodynamic parameters and clinical improvement when using the new technique in a certain group of patients.